A new approach for quantifying phosphorus requirement in Colossoma macropomum using CT scanning - Menezes, Ludmila L. C.; Santos, Janaina G. A.; Guimarães, Igo G.; Padua, Delma M. C.; Machado, Vânia M. V. [UNESP]; Souto, Cristielle N. (Hindawi, 2021)
Available phosphorus (AP) requirement for tambaqui (Colossoma macropomum) was evaluated using different response parameters, and CT scanning was used to determine the adequacy of dietary P along with bone mineralization data. A total of 192 tambaqui juveniles (17 ± 0.85 g) were stocked into 24 70 L-tanks using randomized block design (different floors) with six treatments (1.3, 2.4, 4.8, 6.3, 7.8 and 8.8 g kg−1 AP) and four replicates. Fish were fed ad libitum with six semi-purified diets containing graded levels of AP for 90 days. The dietary AP requirement was estimated using non-linear regression models. No mortality or apparent signs of P deficiency were observed. Increasing dietary AP levels improved all performance variables. Dietary P levels significantly affected bone density. The estimated P requirement for tambaqui was 6.3, 3.68, 5.0 and 6.91 g kg−1 diet for improved weight gain, bone density, vertebrae mineralization and carcass mineral deposition, respectively. CT scanning allowed the visualization of bone structures affected by P deficiency and could predict the P requirement based on vertebrae mineralization. Additionally, blood chemistry parameters were significantly affected by the dietary P level, except for serum calcium. Thus, the use of 6.3 g kg−1 AP in tambaqui diets can maintain normal growth and bone mineralization of juveniles from 17–150 g.
Keywords: bone densitometry; Cachama; carcass mineralization; mineralization of scales; phosphorus nutrition